Importance Of Modern Cosmetology In Medicine: In The Representation Of The Latin Language (Eurasian Journal of Learning and Academic Teaching, 2025)
This article extensively covers the role and importance of modern cosmetology in medicine. The connection of cosmetology with dermatology, plastic surgery, trichology and aesthetic medicine, its development based on innovative technologies and pharmacological drugs are supported by scientific evidence. Current information is provided on the methods of treating skin diseases, rejuvenation through cosmetologically procedures and the safety of their use. The role of the Latin language in cosmetologically terminology is also analyzed